Immigration Supervision of Foreign Citizens Who Abuse The Limited Stay Permit - Argi Nathanael; Herdian Zulfi; Varhan Razzaq (IHSA Institute, 2022)
This study was conducted to deal with the problems of foreigners committing immigration violations, in the form of misuse of limited stay permits. This research was conducted to explore the problems or obstacles that occur in the field in handling cases of abuse of residence permits, especially regarding the misuse of limited stay permits. The large number of foreigners in Indonesia who use a limited stay permit is one of the main scourges in this study. The study in this study focuses on the immigration control and forms of violations of the abuse of limited residence permits committed by foreign nationals who are in Indonesia. This research study was conducted to find out how effective the supervision carried out by immigration was in handling cases of abuse of limited stay permits. Because this has actually been regulated in the immigration law, namely law number 6 of 2011 concerning immigration.